Convolutions of Harmonic Mappings Convex in the Horizontal Direction. (6th September 2021) - Çakmak, Serkan; Yaşar, Elif; Yalçın, Sibel
Abstract : In this paper, we establish some results concerning the convolutions of harmonic mappings convex in the horizontal direction with harmonic vertical strip mappings. Furthermore, we provide examples illustrated graphically with the help of Maple to illuminate the results.